2013
DOI: 10.1371/journal.pone.0067416
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Elevated Monocyte-Platelet Aggregates in Healthy Children

Abstract: Platelets are subcellular fragments which circulate in blood and have well established roles in thrombosis and haemostasis in adults. Upon activation, platelets undergo granule exocytosis and express P-Selectin on the cell membrane which binds a ligand on monocytes, leading to monocyte-platelet aggregation. Elevated circulating monocyte-platelet aggregates in adults are linked to atherothrombosis, but have not been investigated in children where thrombosis is less common. This study aimed to measure monocyte-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 35 publications
2
13
0
2
Order By: Relevance
“…While platelet activation markers as measured by flow cytometry are not used in routine clinical practice, it provides important molecular information about the mechanism of platelet interactions (Michelson et al, 2007). Our previous study (Yip et al, 2013), together with this current study highlights the need to establish age-specific reference ranges for agonist-stimulated platelet activation for interpreting platelet reactivity in children.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…While platelet activation markers as measured by flow cytometry are not used in routine clinical practice, it provides important molecular information about the mechanism of platelet interactions (Michelson et al, 2007). Our previous study (Yip et al, 2013), together with this current study highlights the need to establish age-specific reference ranges for agonist-stimulated platelet activation for interpreting platelet reactivity in children.…”
Section: Discussionmentioning
confidence: 67%
“…We recently reported that circulating MPA are elevated in healthy children compared to adults (Yip et al, 2013). To date, there is limited data of in vitro platelet response to various agonists at sub-maximal concentrations in healthy children.…”
mentioning
confidence: 99%
“…Recent studies confirming different baseline biology of platelets in children compared with adults confirm the need for specific study of all these agents in children. 64 …”
Section: New Biological Targets For Antiplatelet Therapymentioning
confidence: 99%
“…Not approved (pediatric use reported): no pediatric-specific trials ongoing, at least one pediatric case report published. Not approved (no pediatric use reported): no pediatric-specific trials ongoing, no case report published by guest on May 11, 2018 http://circ.ahajournals.org/ Downloaded from studies, the use of novel end points such as net clinical benefit, and the use of novel trial designs, including n of 1 trials and response-adaptive randomization.…”
Section: Considerations For Designing and Performing Pediatric Studiementioning
confidence: 99%
See 1 more Smart Citation